Reinventing Liberty - Price, Fiona (Edinburgh University Press, 2016)
Sir Walter Scott is often regarded as the first historical novelist. Reinventing Liberty challenges this view by returning us to the rich range of historical fiction written in the late 18th and early 19th century. For the first time placing these works in the context of British politics and British history writing, this book redefines the historical novel, revealing a genre which seeks to manage political change through historiographical experimentation. It explores how historical novelists participated in a contentious debate concerning the nature of commercial modernity, the formulation of political progress and British national identity. Ranging across well-known writers, like William Godwin, Horace Walpole and Frances Burney, to lesser-known figures, such as Cornelia Ellis Knight and Jane Porter, Reinventing Liberty uncovers how history becomes a site to rethink Britain as Ôland of libertyÕ.